Evaluation of Common Side Effects of Chemotherapy among Cancer Patients in Khartoum Oncology Hospital Ward, 2019 (Khartoum Journal of Pharmaceutical Sciences, 2021)
The treatment of cancer with most anticancer drugs is complicated by the risk of numeroussevere toxicities,many of which are life-threatening.The toxicities related to anticancer therapiesare the most important factors restricting the use of potentially curative doses.This study aimedto assess the most common chemotherapy side effects developed and their treatment in theKhartoum oncology hospital emergency ward. This study was conducted at the Khartoumoncology hospital's emergency ward from March to May 2019.The data were collected from themedical records and individual interviews with the patients using a structured data collectionsheet. Total of 100 patients were involved in this study, the most common side effects werenausea and vomiting (40%), abdominal pain (29%) of patients, diarrhea (19%), hypotension, fever,body pain, each experienced by (10%) of patients. Febrile neutropenia and dehydration,experienced by (9%) each. Moreover, the most common management of side effects was IVhydration used among 87% of patients, acid suppressants, and antiemetics used among 45% and39% of patients,respectively.Antibiotics were used for 30% of patients; corticosteroids were usedamong 29% of patients.Antispasmodic were used among 27%, and analgesia used for 26 %.Theassociation between the number of chemotherapeutic agents and side effects was signifcant(P=0.023).The study revealed that the most common side effects of chemotherapy were nauseaand vomiting, abdominal pain, and diarrhea.The management mainly by intravenous hydration,antiemetic, acid suppressants, and antibiotics.
Keywords: Cancer; Chemotherapy; Side effect; Emergency ward; Khartoum Oncology Hospital